Psychological Analysis of Children Traumatic Loss by the Main Character in the Novel Bridge to Terabithia - Antonia Meske Fofid; Rosalia Floriani; Sri Winarsih; Nurul Istiqomah; Survey Sijabat (Journal of English Language and Education, 2026)
This study aims to analyze the psychological impact of traumatic loss experienced by the main character, Jess Aarons, in the novel. The research employs a literary psychology approach by applying Elisabeth Kübler-Ross’s five stages of grief, namely denial, anger, bargaining, depression, and acceptance. The primary data are derived from the narrative and dialogues in the novel that depict Jess’s emotional experiences following the death of his close friend, Leslie Burke. The findings indicate that Jess undergoes all five stages of grief. These stages reflect the emotional dynamics of a child in coping with profound loss. Furthermore, the study reveals that Jess is able to endure and achieve psychological recovery through the process of acceptance, while also utilizing imagination as a means of self-healing. This research contributes to a deeper understanding of childhood trauma in literary works and demonstrates how fiction can function both as a reflection of psychological experiences and as a medium for emotional healing among young readers.